Recently isolated food-derived antihypertensive hydrolysates and peptides: A review. (1st June 2021) - Kaur, Arshdeep; Kehinde, Bababode Adesegun; Sharma, Poorva; Sharma, Deepansh; Kaur, Sawinder
Highlights: Isolation and Preparation method of Bioactive peptides. Food sources for Bioactive peptides. Mechanism of bioactive peptides to control hypertension. Abstract: Hypertension is a non-communicable disease characterized by elevated blood pressure, and a prominent metabolic syndrome of modern age. Food-borne bioactive peptides have shown considerable potencies as suitable therapeutic agents for hypertension. The peptide inhibition of the angiotensin I-converting enzyme (ACE) from its default biochemical conversion of Ang I to Ang II has been studied and more relatively adopted in several studies. This review offers an examination of the isolation of concomitant proteins in foods, their hydrolysis into peptides and the biofunctionality checks of those peptides based on their anti-hypertensive potentialities. Furthermore, critical but concise details about methodologies and analytical techniques used in the purification of such peptides are discussed. This review is a beneficial literature supplement for scholars and provides functional awareness material for the food-aligned alternative therapy for hypertension. In addition, it points researchers in the direction of adopting food materials and associated by-products as natural sources for the isolation biologically active peptides.